Integrated reverse left and right ventricular remodelling after MitraClip implantation in functional mitral regurgitation: an echocardiographic study. (26th August 2013) - Giannini, Cristina; Petronio, Anna Sonia; De Carlo, Marco; Guarracino, Fabio; Conte, Lorenzo; Fiorelli, Francesca; Pieroni, Andrea; Di Bello, Vitantonio
Abstract: Aims: The aim of the present study was to investigate the changes of left and right ventricular (RV) dimensions and function after MitraClip implantation in high-risk surgical patients with severe functional mitral regurgitation (MR). Methods and results: Study population included 35 patients with functional MR. All the patients underwent clinical and echocardiographic evaluation at baseline, before discharge and at 6-month follow-up. The mean age was 75 years (63–81), 65.7% ( n = 23) was male with a mean logistic EuroSCORE of 20%. Percutaneous mitral valve repair acronym (PMVR) resulted in significantly reduced MR and improved in New York Heart Association functional class. Echocardiography revealed improvement in left ventricular (LV) size and function since discharge with further improvement at 6 months. During the follow-up, a significant improvement in RV function was also observed by the baseline values. At baseline, before discharge and 6 months, respectively, the tricuspid annulus plane systolic excursion (TAPSE) was 16.8 ± 3.9, 18.7 ± 3.4, and 19.3 ± 4.5 mm ( P = 0.001); the systolic pulmonary artery pressure (SPAP) was 50.1 ± 6.8, 41.2 ± 6.8, and 38.1 ± 6.8 mmHg ( P < 0.0001); and the systolic velocity at the tricuspid annular (RV-Sm) was 8.8 ± 2.9, 10.4 ± 3.5, and 17.7 ± 3.1 cm ( P < 0.0001). Conclusion: MitraClip implantation induces a significant reverse remodelling of LV, with reduction in both diastolic and systolic LV volumes and an increase in the cardiac index. The concomitant reduction in LV filling pressure, obtained after MitraClip implantation, reflects nearly immediately on the haemodynamics of the right sections. In fact, since discharge, we observed both a reverse remodelling of the right sections, with a significant reduction in SPAP, and a significant increase in longitudinal RV systolic function as shown by the increase in TAPSE and RV-Sm.